The profession of Sociology from the perspective of its actors - Varea, Soledad (2022)
This article deals with the profesional field of sociology from the perspective of the actors. Thus, in – depth interviews are conducted with sociologist from different promotions and generations. Likewise, documentos written by teachers of the faculty are reviewed.